The psychosocial effects of severe caries in 4-year-old children in Recife, Pernambuco, Brazil - Sandra Feitosa; Viviane Colares; Jimmy Pinkham (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
The aim of this study was to analyze the psychosocial effects of severe caries in 4-year-old children in Recife, Pernambuco, Brazil. The clinical examination was conducted by a single examiner in order to select children with severe caries and caries-free (kappa = 1). Of the 861 children examined, 77 (8.1%) had severe caries and 225 (23.6%) were caries-free. Data were collected by applying validated questionnaires answered by the parents or guardians. Most of the parents or guardians of children with severe caries reported that their children complained of toothache (72.7%), and a significant portion stated that their children had problems eating certain kinds of food (49.4%) and missed school (26.0%) because of their teeth. Most of the parents or guardians of children with severe caries (68.8%) stated that oral health affects their children's life, while the same was stated by 9.8% of the parents or guardians of the caries-free children. Severe caries was found to have a negative impact on children's oral health-related quality of life.